Energy interaction strategy for multi-prosumer distribution systems based on game theory - Lou, Wei; Zhu, Shenglong; Zhuo, Xu; Qin, Shaorui; Li, Baodong; Zhou, Ya; Chen, Jian; Gao, Qiang (Frontiers in Energy Research, 2025)
In flexible distribution systems, the strong uncertainty of generation and load demand poses challenges for energy interaction and resource coordination. However, existing energy interaction strategies generally focus only on economic benefits, neglecting safety performance, and are insufficient to ensure the reliable operation of the system. To address these issues, this paper proposes an energy interaction strategy for multi-prosumer flexible distribution systems, considering the economic benefits of all parties and the voltage safety of the system. First, a multi-agent energy interaction framework based on the Stackelberg game is established, and a bi-level optimization model for the distribution network operator and prosumers is constructed. Second, the paper innovatively introduces soft open point-based power flow control technology into the energy trading market. Then, the KKT conditions, dual theory, linearization, and relaxation techniques are applied to transform the original bi-level game problem into a single-level mixed-integer second-order cone programming problem, improving computational efficiency. Finally, the improved IEEE 33-bus distribution system is simulated and compared with two other scenarios. The results show that the proposed strategy can significantly improve the economic and safety performance of the energy interaction system, optimize the power flow distribution, and effectively enhance power quality. The approach offers a promising solution to the growing challenges of managing distributed energy resources in the context of flexible and reliable grid operation.